Secularization and social sense of religion - Bacevičiūtė, Danutė (Religija ir kultūra, 2011)
This article deals with the question of religion in contemporary secular world, to be precise – the main questions are: what mean political and ethical aspects of religion which are in the focus of contemporary secular world, and what is the social sense (meaning) of religion? The author tries to answer these questions and to find theoretical origins of such attitude toward religion by analyzing the interpretations of religion in Immanuel Kant and Jürgen Habermas. Both philosophers envisage the sense of religion in its social purpose. Kantian project of moral religion and Habermas’ endeavor to overcome social disintegration, reviving the dialog between reason and religion, have been interpreted not only as the process of reduction of religion into social plane and an act of appropriation of the religious. One can see that both thinkers encounter the social contingency as the phenomenon (or prophenomenon) which itself is not very clear but appears as grounding the social sense of religion. Therefore the author comes to conclusion that social sense of religion in the secular situation means not only appropriation of the religious (immanentization) but also reveals social relationship as that which calls for religious sense (transcendence in immanence).
Keywords: Kant; Habermas; social sense of religion; social contingency